LET dependence of the yield of single-, double-strand breaks and base lesions in fully hydrated plasmid DNA films by 4He(2+) ion irradiation. - Urushibara, A; Shikazono, N; O'Neill, P; Fujii, K; Wada, S; Yokoya, A (2008)
PURPOSE: To characterize the complexity of DNA damage through determination of the yields of single (SSB) and double strand breaks (DSB), base lesions and clustered damage sites induced in fully hydrated plasmid DNA by direct radiation effects as a function of the ionizing density of the radiation using 4He(2+) ion irradiation with linear energy-transfer (LET) values in the range 19 to 148 keV/microm. MATERIALS AND METHODS: Hydrated plasmid DNA (pUC18) containing 34.5 water molecules/nucleotide was irradiated with He(2+) ions with LET values of 19, 63, 95, 121 and 148 keV/microm. From quantification of the conformational changes of the irradiated samples (closed circular, open or linear forms) analyzed by agarose gel electrophoresis, the yields of SSB and DSB were obtained. Base lesions were visualized as additional strand breaks by treatment with base excision repair enzymes (endonuclease III (Nth) and formamidpyrimidine DNA glycosylase (Fpg)). RESULTS: The yield of prompt SSB does not depend significantly on LET of the 4He(2+) ions, whereas the yield of prompt DSB increases with increasing LET. The yields of isolated base lesions, revealed by Nth and Fpg as additional SSB, decrease drastically with increasing LET. The sum of the yields of DSB and additional DSB revealed by Nth and Fpg increase with increasing LET of the 4He(2+) ions except at the highest LET investigated. CONCLUSION: The yields of clustered damage, revealed as DSB and non-DSB clustered damage sites, but not isolated lesions, namely SSB, increase with increasing ionization density of the 4He(2+) ions except at the highest LET investigated.